Keterampilan Smash Bola Voli Ekstrakurikuler SMPN 2 Bua Ponrang : Peran Kondisi Fisik - Tanjung, Enha Syahrul; Hidayat, Rachmat; Nasriandi, Nasriandi (Jurnal Porkes, 2025)
The purpose of this study was to determine the role of physical condition on volleyball smash skills. This research method uses quantitative methods with descriptive correlational research design. The number of samples used in this study were 14 students at SMPN 2 Bua Ponrang. The population in this study were all extracurricular students of SMPN 2 Bua Ponrang. The results of statistical analysis of the prerequisite test (normality test) obtained a physical condition value of 0.989 with a significant level of 0.999 or 0.999> 0.05 and a smash skill value of 0.946 with a significant level of 0.498 or 0.498> 0.05, so it can be said that the physical condition value and smash skill value are normally distributed. The results of the linearity test of physical condition data on smash skills with an F value of 2.670 and a significant level of 0.447 are greater than α 0.05, so it is said to be linear. From the results of the regression test data analysis, the F value is 22.324 and the significance value is 0.000. Because the calculated F value (22.324)> (4.725) and the significance value is smaller than 0.05 (0.000 <0.05), then H1 is accepted which indicates that physical condition has a significant influence on students' extracurricular smash skills. It is concluded that physical condition has a significant role in students' volleyball smash skills at SMPN 2 Bua Ponrang.